The pion-kaon scattering amplitude and the K 0 ∗ 700 $$ K_0^{* }(700) $$ and K ∗(892) resonances at finite temperature - A. Gómez Nicola; J. Ruiz de Elvira; A. Vioque-Rodríguez (Journal of High Energy Physics, 2023)
Abstract We perform a complete calculation of the pion-kaon scattering amplitude in Chiral Perturbation Theory at finite temperature, paying particular attention to the analytic structure of the amplitude and the main differences with respect to the zero temperature case. We also extend the Inverse Amplitude Method at finite temperature for unequal-mass scattering processes, which allows us to unitarize the amplitude and obtain the thermal evolution of the K 0 ∗ 700 $$ K_0^{* }(700) $$ and K ∗(892) pole parameters. As a direct application of our analysis, we show that the thermal evolution of the K 0 ∗ 700 $$ K_0^{* }(700) $$ resonance is crucial to explain the behavior of the scalar susceptibility for isospin I = 1/2, which in turn, is directly connected with chiral and U(1) A restoration properties of the QCD phase diagram.